(3GdGfJUGQ dhGSWI YbO GdCeUGQs - (3EHQGgje Hf eMeO Hf CjOeQ GdYdGFj GdSQGLj, GHf ObeGb , UGQe GdOjf ,J (B809 (3g` s
(3ChdgG (B:s
(3hCeG bQGge aChdge CHShL hYHQJgG NeSI BdGa OjfGQ s
(3BNQgG (B:s
(3GdefHO ef Mbhb GdHYdi bUhQ jQb Mb GdMOjf KeQI GdcQhe s
(3ef GdfSNI faSgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B64 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B86s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B50 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B50 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B27 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JGQjN (B1244) s
Keywords: (3GdJGQjNs